The gap between Parmenides’ argument on Being and his cosmology in the Aristotelian account - Loureiro Conte, Bruno (Revista Archai, 2023)
In some of the Aristotelian accounts, Parmenides’ thesis is construed in opposition to the philosophy of nature; on the other hand, he is also depicted, in a different context, as a cosmologist, to whom the Stagirite (and a long tradition afterwards, ending with Simplicius) ascribes a theory of becoming and its principles. In this paper, I exhibit and analyse the relevant passages from Physics I 1-3, Metaphysics I 3 and 5 and On generation and corruption I 3, providing an interpretation that aims to solve the apparent paradox, making sense of the information we can gather from Aristotle’s and Simplicius’ testimonies. Eventually, I propose a construal of the Two Ways of fr. 2 with an emphasis on the predicative reading of einai, which could hint at the Parmenidean approach to cosmology that runs in parallel with the argument on Being.